Relationship between Birthweight of Newborns and Nutritional status of Pregnant women in Maternal Teaching Hospitals in Mosul City - Jwan Mohammad Hassan, Salwa Hazim Almukhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aims of the study are to compare the impact of a mother's maternal nutritional status during her pregnancy on baby's birth weight. Methodology: The present study was done conducted from 1st November 2019 to 1st March 2020, including 150 pregnant women in antenatal care at the departments of Obstetrics and Gynecology in two maternal hospitals in Mosul city. The assessment of the nutritional status of all antenatal mothers was done by interrogation with a pretested structured questionnaire. Hemoglobin level was determined in a laboratory, determine BMI and gestational weight gain. All the mothers were followed till the term for pregnancy outcome particularly for baby weight. Statistical Package for the Social Science (SPSS, version 25) is used for data analysis. Results: In present study, mostly, 50(33.3%) of the women belonged to the maternal age group of 25-30 years followed by 45(30.0%) woman who are between <30 years of age. Majority of the mothers have primary education 73(48.7%) who belong to socio economic class II and (90.0%) are house wives by occupation. Distribution of parity reveales that maximum cases are multipara 78 (52.0%).There are 43(28.7%) of infants born with >2500gm. In the present study, statistical analysis of the study variables shows that there are significant differences between gestational weight gain and birthweight which are mean±SD of weight gain during 2nd trimester (3.29±3.68) and 3rd trimester (3.97±4.51). But no significant during 1st trimester. Maternal pre-pregnancy BMI significant correlation with BW at P = 0.005, and significantly association between Hb% level and birthweight at P=0.000 during three trimester. Recommendations: Community-based research is needed to evaluate the prevalence and common anaemia predictors, as well as the forms of anemia based on red blood cell morphology in pregnant women's population. It will help to organize health care programs, minimize maternal morbidity and mortality, and contribute to improving women's well-being in society at large.